Globalisation : trends, issues and macro implications for the EU - Denis, Cecile; McMorrow, Kieran; Roger, Werner; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
Globalisation, defined as an increasingly integrated world economy, has the potential to generate the largest structural upheaval in economies since the industrial revolution. As in the past, this process is being underpinned by both technological change and by a shift in policies in many countries towards a more open, market based, system of economic governance. These policies reflect the realities of a new world order where knowledge creation and absorption and the flexibility of the regulatory and institutional frameworks will be the key determinants of the economic fortunes of economies. This paper examines the historical empirical evidence regarding globalisation and quantifies the macro benefits and costs for the EU over the coming decades.
Περιέχει βιβλιογραφία
Economic Papers